PERIBAHASA DORABOLOLO TERNATE: SEBUAH INOVASI DALAM PENDIDIKAN - Nurbaya, Nurbaya (Jurnal Pendidikan dan Ekonomi (JUPEK), 2024)
Proverbs are traditional expressions of a society. The application of the Ternate ethnic dola bololo proverb in learning as an innovation in the field of education. The purpose of writing this article is to discuss the use of proverbs in education, especially in Indonesian language and literature education, and to explain the advantages of the proposed method and its procedural aspects. The research method is descriptive qualitative. The results of the study explain the application of proverbs in learning and the application of proverbs for education and learning. The author also explains that this method is more suitable for secondary school levels in Ternate City.